On Convergence of a Least-Squares Kansa's Method for the Modified Helmholtz Equations (Advances in Applied Mathematics and Mechanics, 2018)
We analyze a least-squares  asymmetric radial basis functioncollocation method for solving the modified Helmholtz equations. Inthe theoretical part, we proved the convergence of the proposedmethod providing that the collocation points are sufficiently dense.For numerical verification, direct solver and a subspace selectionprocess for the trial space (the so-called adaptive greedyalgorithm) is employed, respectively, for small and large scaleproblems.